Analisis Kepuasan Pengguna Terhadap Penggunaan E-Payment Universitas Menggunakan Metode EUCS dan TAM - Widyawati, Nilu Gede; Purnama, Benni; Mulyono, Herry (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Dinamika Bangsa University E-payment website is an information system developed by UNAMA's IT Division in 2020 and is used to confirm online tuition payment transactions. the results of observations and interviews conducted with several students indicate that the Dinamika Bangsa University e-Payment website still has several problems in its use, namely the information on the web is incomplete, for example there is no information about the rules for writing NIMs andThe name on the payment receipt paid via ATM and e-banking.This study aims to determine the satisfaction level of the UNAMA E-payment website and to determine the effect of the relationship between research variables using the End User Computing Satisfaction (EUCS) and Technology Acceptance Model (TAM) web e-Payment methods at Dinamika Bangsa University. This study uses path analysis as a data analysis technique with the help of SPSS software version 26. based on the analysis of the data that has been described, it can be see that of the 7 research variables which contain 6 research hypotheses, the variables content, accuracy, ease of use, and timeliness are stated to have a positive and significant effect on the attitude toward using variable. Besides that, the attitude toward using variable also has a positive and significant effect on user satisfaction variable. The rejected hypothesis is the relationship between the format variable and the attitude toward using variable.